DESIGN OF FRAME FOR THE PUMP PERFORMANCE TEST EQUIPMENT USING VDI 2221 METHOD - Muhamad Fitri; Frelly Rizqiansyah (Universitas Mercu Buana, 2022)
Pumps in modern human life have become a major need, and their use is very wide, therefore pump learning is indispensable for mechanical engineering students. For pump performance learning media, Pump Performance Test Equipment (PPTE) is needed. The test equipment requires a strong frame and meets the requirements to be able to withstand the load, not only the equipment load but also the water weight used as the working fluid on the performance test equipment which is very large. This study aims to design a frame that can withstand the entire load of the PPTE. The design is done by calculating the load experienced by the frame when the test equipment is operated. The design of this pump performance test framework uses the VDI 2221 method, which includes several stages: task clarification, design concepts, concept embodiment, and design details. The results obtained from the use of the VDI 2221 method are variation 1, with a frame of 1000mm length, 1200mm width, and 1140mm height. The frame specifications using 4x4 hollow steel size with a thickness of 2mm and 4x6 size with a thickness of 3mm, and using a wheel type with a lock that can withstand the load. maximum up to 600kg.